Analisis Kinerja Tenaga Kesehatan Di RSUD Kabupaten Banyuasin - Fauta, Ari; Oktriyedi, Ferly; Sitorus, Rico Januar (JURNAL SMART ANKes, 2023)
The national health system is essentially an order that reflects the efforts of the Indonesian people to improve the ability of health degrees which emphasizes that the goal of national development is to improve the quality of human resources. HR performance is a term that comes from the word Job Performance or Actual Performance (job performance or actual achievement achieved by someone). The design in this research is a cross sectional study. With a population of health workers working in the Banyuasin District Hospital amounting to 170 people and a sample of 170 people using the Total Sampling Technique. Bivariate data analysis using Chi Square and Multivariate using multiple logistic regression. The results showed that most of the characteristics were young age (52.9%), female gender (69.4%), education < Non Sarjana (61.2%), not civil servants (84.7%), married (82.4 %), have worked for a long time (88.8%), good working environment conditions (50.6%), good job security (55.3%), good rewards (51.8%), good performance ( 50.6%). There was no relationship between respondent's age (p= 0.122), gender (p= 0.691), education (p= 0.506), employment status (p= 0.781), marital status (p= 0.350), length of work (p= 0.358) with the performance of health workers. There is a relationship between working environment conditions (p= 0.0001; OR=5,148), job security (p= 0.0001; OR=10,938), rewards (p= 0.0001; OR=9,300) and the performance of health workers. The most dominant variable is job security (p=0.0001;OR=6,240). Suggestions as a source of reading about improving performance in the Banyuasin District Hospital and other hospitals of the same type.